Challenges in digital forensics. (3rd March 2016) - Vincze, Eva A.
Abstract: Various terms have been used to describe the intersection between computing technology and violations of the law-including computer crime, electronic crime, and cybercrime. While there remains little agreement on terminology, most experts agree that the use of electronic devices to commit crime has increased dramatically and is now commonplace. It is the role of the digital investigator to bring cybercriminals to justice. Cybercrime however differs from traditional crime and presents a variety of unique challenges including the variety of electronic devices available, amount of data produced by these devices, the absence of standard practices and guidelines for analyzing that data, the lack qualified personnel to perform investigations and the lack of resources to provide on-going training. This paper examines these challenges